The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1159/000201356
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Viability of the Isolated Vascularly Perfused Rat Colon

Abstract: The colon contains large numbers of endocrine cells. Insight into their physiological function is limited. This is due to the fact that no sufficient model of isolated endocrine colon cells is available. In the present study we introduce an isolated vascularly perfused colon model for in vitro studies. This model offers the advantage that it keeps the endocrine cells in their physiological orientation and environment. The gut mucosa is highly sensitive to ischemia. Therefore, a careful validation of its viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Both glucosidase inhibitors clearly had the ability to enhance the release of GLP-1 from the lower intestine significantly. That the L cells of the lower intestine are capable of releasing the gut peptide upon luminal stimulation has also been demonstrated by in vitro experiments with isolated bowel segments [18].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Both glucosidase inhibitors clearly had the ability to enhance the release of GLP-1 from the lower intestine significantly. That the L cells of the lower intestine are capable of releasing the gut peptide upon luminal stimulation has also been demonstrated by in vitro experiments with isolated bowel segments [18].…”
Section: Discussionmentioning
confidence: 76%
“…In the in vitro system, glucose was able to enhance GLP-1 secretion in the venous effluent [18]. In the in vivo situation, instillation of glucose into the distal large bowel was not able to enhance GLP-1 to a significant extent in plasma, although the human rectum contains the largest amount of GLP-1-producing L cells [5].…”
Section: Discussionmentioning
confidence: 88%
“…The model of an isolated, vascularly perfused rat colon has been described in detail elsewhere [21,22]. Each colon preparation was used just for one perfusion trial.…”
Section: Preparation Of the Isolated Perfused Rat Colonmentioning
confidence: 99%
“…It has been shown that the vagal nerve mediates the early response of L cells to nutrients in rats (21). Among the different neuromediators previously tested for their capacity to stimulate GLP-1 release, carbachol, a cholinergic agonist, and GRP were shown to stimulate GLP-1 release in cellular and organ models (7,8,22). NCI-H716 cells incubated during 2 h with increasing concentrations of carbachol showed a dose-dependent increase in GLP-1 release, with a maximum of 1.5 Ϯ 0.2-fold at the maximal dose tested (1 mm; Fig.…”
Section: The Neuromediator Gastrin-releasing Peptide (Grp) and The Chmentioning
confidence: 99%